Especies arborescentes del género Blechnum (Blechnaceae-Polypodiophyta) - Rolleri, Cristina Hilda (2013)
Arborescent species of the genus Blechnum (Blechnaceae: Pteridophyta). Although the genus Blechnum has been largely studied, problems of species characterization, nomenclature, classification and taxonomy remain unsolved. For these reasons, in this study we intend to deepen in the characterization of the arborescent group of Blechnum with a review of eight species: B. brasiliense, B. columbiense, B. cycadifolium, B. magellanicum, B. moritzianum, B. schomburgkii, B. tabulare and B. werckleanum.Type material and several collections from diverse herbaria were studied. For morphological studies we used both herbarium and fresh material collected by the authors in fieldwork between 2005 and 2010. Rhizomes, stipes, vascularization of costae, as well as several characters of the lamina, such as outline, division, venation, margin structure, epidermal patterns, stomata, presence and types of hypodermis, and mesophyll of pinnae were studied. Important aspects of the morphology of the sporophyte have been analyzed, and external characters have been correlated with internal diagnostic ones to use the most reliable external traits in keys and descriptions. Taxonomy has been updated, and corrections have been introduced to the species nomenclature and comments were included to summarize the current knowledge of the geographical distribution and ecology. The presence of B. tabulare in America is confirmed, and the taxonomy of the species is updated, since external and internal morphology indicated that other related, American and African species, such as B. spannagelii and B. madagascariense must be included under that name. Similar studies carried out on B. schomburgkii indicated that the name is a synonym of B. auratum subsp. auratum, while B. auratum subsp. columbiense is treated here as a well characterized species. Detailed study of numerous specimens allowed to characterize B. moritzianum, being the correct name to apply to the recently described B. yungense. A refreshed description of the species is presented together with a list of new, selected materials to illustrate current known geographical distribution. Expanded data on ecology, geographical distribution and affinities are given, and a key for species identification is presented.